A comprehensive review of uncommon EGFR mutations in patients with non-small cell lung cancer. (December 2017) - Tu, Hai-Yan; Ke, E-E; Yang, Jin-Ji; Sun, Yue-Li; Yan, Hong-Hong; Zheng, Ming-Ying; Bai, Xiao-Yan; Wang, Zhen; Su, Jian; Chen, Zhi-Hong; Zhang, Xu-Chao; Dong, Zhong-Yi; et al.
Highlights: Uncommon EGFR mutations are more prevalent in males and smokers. The most prevalent uncommon mutation is 20INS (31%) followed by G791X (21%). Chemotherapy might be better than TKIs for 20INS, T790 M and worse for other mutations. Abstract: Introduction: Patients with non-small cell lung cancer (NSCLC) harboring uncommon epidermal growth factor receptor ( EGFR ) mutations are a heterogeneous group exhibiting differential responses to EGFR inhibitors. This retrospective study reviews the prevalence of uncommon EGFR mutations in a Chinese NSCLC cohort and the clinical characteristics and efficacy of EGFR tyrosine kinase inhibitors (TKIs) associated with these patients. Materials andMethods: A total of 5363 lung cancer patients were screened and underwent EGFR genotyping at the Guangdong Lung Cancer Institute. Of those with uncommon EGFR mutations, the clinical characteristics and responses to EGFR-TKIs were reviewed retrospectively. Results: Uncommon EGFR mutations were observed in 218 patients, comprising 11.9% of all patients with documented EGFR mutations. More smokers (30.7% vs. 24.3%, P  = 0.039) and males (54.1% vs. 44.4%, P  = 0.007) were among the patients with uncommon mutations compared with common mutations. The most frequent uncommon mutations were exon 20 insertions (30.7%, n = 67), followed by G719X mutations (21.1%, n = 46) and compound L858R mutations (17.0%, n = 37). Favorable efficacy was observed in patients harboring compound L858R or G719X mutations, with a median progression-free survival (PFS) of 15.2 (95% CI: 8.7–21.7) or 11.6 (95% CI: 3.6–19.6) months, respectively. The median PFS of those with the T790 M mutation or an exon 20 insertion was 1.0 (95% CI: 0.0–2.2) and 3.0 (95% CI: 1.3–4.7) months, respectively. Conclusion: This study reviewed the prevalence of uncommon EGFR mutations and their sensitivity to EGFR-TKIs. Favorable responses were observed in patients with G719X and compound L858R mutations, indicating that they may benefit from EGFR-TKIs as a first-line therapy.